Changing user motivations for social networking site usage: implications for internet advertisers. (1st January 2012) - Gangadharbatla, Harshavardhan; Hopp, Tobias; Sheehan, Kim
Why do people use social network sites (SNSs) such as Facebook? Researchers have examined motivations for SNS usage from a uses and gratifications perspective, either by looking at text-based bulletin boards or online communities, or by focusing on a small group of total users (e.g., college students). Both streams of research show individuals can have more than one motivation for using these sites. However, contemporary research has generally failed to examine how user motivations evolve over time. This study builds on existing research by examining both initial and subsequent motivations to join SNSs, specifically Facebook. The results indicated that users initially joined Facebook for a variety of social, information-seeking, and bandwagon reasons. As users spent more time on Facebook, it became apparent that use of the site was primarily motivated by a need to belong and interpersonal communication motivations. These results are placed into the advertising context and implications for both advertisers and advertising researchers are discussed.